OPTIMALISASI SENI MUSIK DALAM PENDIDIKAN ISLAM - Rosyada Ayu Fatimah; Yazida Ichsan; Utut Abdillah Iskandar; Riska Anisa Indriyani; Wahyu Lestari (Pascasarjana Institut Seni Indonesia Padang Panjang, 2022)
This paper describes the optimization of art in Islamic education. The source of the idea comes from various journal literature. By using a literature study approach, this research shows that the position of art in Islam has a very important role, because art is a part of culture that cannot be separated from education. Therefore, in the context of Islamic education, especially in Islamic educational institutions, art must continue to be preserved through various creative activities. An ideal extensionist at least masters the map of da'wah, understands the characteristics of the community and is rich in da'wah methodologies. So that the message conveyed to the people is easy to accept and succeed. The characteristics of the majority community in Indonesia are, they like all things that smell like art from the young to the old. Da'wah wrapped in art has been widely used by preachers, for example, music, puppets, theater, and many others. There is a lot of evidence of the success of art in da'wah methods such as music, this da'wah method is suitable for all people from the young to the young, this da'wah method is very popular with Preacher because it brings a cheerful and fun atmosphere and is easily absorbed by listeners in Islamic values that contained in the song that is sung. The brain development approach is an important concern in the care and development of early childhood because as it has been previously known that the brain controls human life. This study aims to determine the urgency of art learning in optimizing early childhood learning in field observation studies. Individuals engaged in art can increase spontaneity and self-expression, control limited inhibitory effects, and produce creative work.